Study of health seeking behavior of dog bite victims and a comparison of the effectiveness of different interventions on canine immunization coverage in four PHI areas in Colombo district - Damboragama, S..N (My University, 1999)
This community based descriptive study was carried out to determine the health seeking behavior of people following an animal bite, their knowledge and attitudes towards rabies and to evaluate the present immunization services for rabies control in the canine population. This study suggest that immunization coverage and the knowledge on rabies can be improved by carrying out a planned health education campaign prior to a mass vaccination programme in the community, within the existing infrastructure of the department of health services without added cost. Changing the times of service delivery too can improve the coverage. It also identified that useful information can be obtained on quality of services by developing simple tools.(eg. check list)